Fundamentals of air pollution - Vallero, Daniel A. (Elsevier Science, 2014)
Fundamentals of Air Pollution is an important and widely used textbook in the environmental science and engineering community. This thoroughly revised fifth edition of Fundamentals of Air Pollution has been updated throughout and remains the most complete text available, offering a stronger systems perspective and more coverage of international issues relating to air pollution. Sections on pollution control have been reorganized and updated to demonstrate the move from regulation and control approaches to green and sustainable engineering approaches. The fifth edition.